2020
DOI: 10.1111/cgf.13925
|View full text |Cite
|
Sign up to set email alerts
|

Expression Packing: As‐Few‐As‐Possible Training Expressions for Blendshape Transfer

Abstract: To simplify and accelerate the creation of blendshape rigs, using a template rig is a common procedure, especially during the creation of digital doubles. Blendshape transfer methods facilitate copy and paste functionality of the blendshapes from the template model to the digital double. However, for adequate personalization, such methods require a set of scanned training expressions of the original actor. So far, the semantics of the facial expressions to scan have been defined manually. In contrast, we formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Additionally, we found that some facial action units were more perceptually noticeable than others, and provide a table showing the order of importance (Table 2). This perceptual ordering will be useful for game developers for tasks that require an order of blendshapes, such as level-of-detail blendshape reduction methods [Costigan et al 2016], or example creation for blendshape transfer [Carrigan et al 2020]. By identifying and removing blendshapes of lower visual saliency, which equates to simply removing rows from the blendshape matrix, we can save both memory and computation required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we found that some facial action units were more perceptually noticeable than others, and provide a table showing the order of importance (Table 2). This perceptual ordering will be useful for game developers for tasks that require an order of blendshapes, such as level-of-detail blendshape reduction methods [Costigan et al 2016], or example creation for blendshape transfer [Carrigan et al 2020]. By identifying and removing blendshapes of lower visual saliency, which equates to simply removing rows from the blendshape matrix, we can save both memory and computation required.…”
Section: Discussionmentioning
confidence: 99%
“…games and other real-time applications, with the aim of reducing the number of blendshapes needed for animating a rig [Costigan et al 2016], or prioritising which blendshapes to include in expressions for example-based rig creation algorithms [Carrigan et al 2020]. Additionally, algorithms that create or alter facial geometry are usually evaluated against ground-truth facial meshes using standard geometry error metrics, however, we postulate that standard error-metrics may not be sufficient to determine how perceptually different the results are to the ground-truth.…”
mentioning
confidence: 99%
“…To build robust face rigs, we need to reconstruct a dynamic expression model that faithfully captures the subject's specific facial movements. A full set of personalized blendshapes for a specific subject can be built from 3D scan data of the same subject [Carrigan et al 2020;Huang et al 2011;Li et al 2010;Weise et al 2009;Zhang et al 2004]. These methods can reconstruct expressions that capture the target's personal expressions, but a large set of action units or sparse expressions are required as input.…”
Section: Related Workmentioning
confidence: 99%
“…There are many reasons behind this, from the growth in computational power to the economic benefit of using a parametric model to simulate physical phenomena. Today, 3D models serve many fields, including animation of characters [ 1 ] and faces [ 2 , 3 , 4 ], recognition of expressions [ 5 ], face recognition [ 6 ], and inferring body shapes and measurement to be used, for example, in the clothing industry, for virtual try-on [ 7 ], or in the medical field to estimate fat distribution. However, the applications are often limited due to privacy and sensitive information constraints that reduce or block data sharing and aggregation from multiple sources.…”
Section: Introductionmentioning
confidence: 99%